OP0286 Genotypic effects of ankylosing spondylitis associated il7r polymorphisms are mediated through monocytes in inflammation. (12th June 2018) - Al-Mossawi, M.H.; Lau, E.; Danielli, S.; Yager, N.; de Wit, J.; Mahe, E.; Rizvi, L.; Knight, J.; Fairfax, B.; Bowness, P.
Abstract : Background: Interleukin 7 (IL-7) plays a key role in T cell survival and proliferation. Both cell-surface expressed and soluble forms of the IL-7 receptor (sIL7R) are recognised. sIL7R has been shown to prolong IL-7 activity in inflammation(. 1 IL7R polymorphisms are associated with multiple inflammatory diseases including ankylosing spondylitis(AS). Higher levels of circulating sIL7R are present in those carrying the risk variant but the cellular sources of soluble IL7R are unclear. Expression quantitative trait loci (eQTL) studies have shown genetically regulated IL7R gene upregulation in monocytes after innate immune stimuli(. 2 Objectives: This study aims to characterise the genotypic effects of IL7R polymorphism on monocyte protein surface expression and sIL7R release. Methods: Monocyte cell surface IL7R expression was measured by flow cytometry in the presence or absence of LPS or TNF in a cohort of volunteers recruited from the Oxford biobank. Soluble IL7R was quantified by ELISA in purified monocyte cultures stimulated with LPS. RNA sequencing was performed for 8 paired samples of control and recombinant IL-7 exposed stimulated monocytes. Results: Surface IL7R expression was induced after 24 hours of LPS stimulation both in isolated monocytes (n=84, p=<8.9e-19) and CD14 +cells in whole PBMC cultures (n=103, p=<3.9e-31). We find the key genotypic regulator of this response to be rs6897932, previously associated with AS predisposition, both in isolated monocytes (n=85, p=9e-7) and CD14 +cells in whole PBMC cultures (n=103, p=9.4e-5). There was no genotypic effect seen in unstimulated monocytes. Notably IL7R positivity of CD4+, CD8 +and CD56+cells measured within the PBMC culture both before or after LPS stimulation showed no association with rs6897932. The addition of anti-TNF (Infliximab) abrogated the genotypic effect. In a second independent cohort, genotype-specific surface IL7R induction was also observed after stimulation with recombinant human TNF (n=62, p=0.0007). In a third cohort, release of soluble IL7R was observed to be under genetic control after stimulation with LPS (n=99, p=<3.1e-11). RNA sequencing of isolated monocytes stimulated with LPS and recombinant IL-7 showed differential expression of 3240 transcripts (FDR<0.05) compared with LPS alone (n=8). Direct ex-vivo staining of monocytes from inflamed synovial fluid of SpA showed significant upregulation of IL7R compared to paired PBMC monocytes (n=4, p=<0.015). Conclusions: Monocytes upregulate IL7R expression and soluble IL7R secretion after LPS treatment in a functional, genotype- and TNFalpha-dependant manner. SpA synovial monocytes express IL7R suggesting preactivation. These data draw attention to an unappreciated key myeloid role for AS risk variants at IL7R. References: [1] Lundström W, et al. PNAS 2013. [2] Fairfax BP, et al. Science 2014. Acknowledgements: BPF and PB contributed equally to this work Disclosure of Interest: None declared